Accelerated biological ageing as a complication of cancer therapy - O. O. Kovalov; M. Yu. Kolesnyk; O. V. Hancheva; I. F. Bielenichev; K. O. Kovalov (Zaporožskij Medicinskij Žurnal)
Aim. The paper aimed to update the study on accelerated biological aging as a complication of cancer therapy with a focus on diagnosing and prognosing the disease course.